Konstruksi “Bocor Alus Politik” Tempodotco terhadap Manajemen Komunikasi Pemerintahan Prabowo - Maida, Serepina Tiur; Enrieco, Edward; Sartika, Rawit; Pranawukir, Iswahyu; Alamsyah, Alamsyah (Jurnal Cyber PR, 2025)
This study aims to analyze how Tempodotco, through the program “Bocor Alus Politik,” constructs the representation of communication management in the Prabowo Subianto administration, specifically through the episode titled “Sjafrie Sjamsoeddin di Antara Manuver Politik dan Komunikasi Ruwet Prabowo.” The approach employed is qualitative content analysis, examining narrative messages, diction, framing, and political symbols presented in the episode. The focus of the analysis is on how Tempodotco narrates the dynamics of political communication within the elite circles of government, including communication strategies, discourse conflicts, and the leadership image of Prabowo constructed through digital political journalism narratives. The findings indicate that “Bocor Alus Politik” does not merely provide information but functions as a discursive space framing the government as an entity characterized by intrigue and complex internal communication. The framing presented by Tempodotco constructs the image of the Prabowo administration as a figure with fragmented yet strategic communication, revealing the dialectics between loyalty, pragmatism, and efforts to maintain post-election political stability. This study contributes to the study of digital media political communication by highlighting the role of media in shaping public perception of the governance and communication management of a new administration.